Pengaruh Tingkat Pendidikan, Upah Minimum, Dan Tingkat Pengangguran Terbuka Terhadap Persentase Bekerja Di Sektor Formal Di Indonesia - Elfando Jafendra; Fandy Triawan (Universitas Negeri Padang, 2026)
The percentage of workes in the formal sector represents the proportion of the labor force absorbed into the structured labor market and protected by labor laws and regulation. This study aims to analze the partial and simultaneous effects of education level, minimum wage, and the open unemployment rate on the percentage of workers in the formal sector in Indonesia. The quantitative data used in study is secondary panel data sourced from publications by Statistics Indonesia (BPS) and the Ministry of Manpower for the period 2020 to 2024, covering 34 provinces in Indonesia with a total of 170 observations. The panel data regression estimation result show that, partially, the level of education has a positive and significant effect on the percentage of workes in the formal sector, the minimum wage has a significant positive effect in linewith regional labor market dyamics, and the open unemployment rate has a positive but insignificant effect, whereas simultaneously all three independent variables have a significant effect on the percentage of formal sector workers in Indonesia. These findings emphasize the importance of integrated government policymaking to enhance human capital quality through education, establish balanced minimum wage policy formulations, and reduce unemployment rates in order to expand formal sector employment absorption that is more productive and sustainable across all regions in Indonesia.